2018
DOI: 10.1891/1058-1243.27.1.50
|View full text |Cite
|
Sign up to set email alerts
|

First-Time Mothers’ Experiences of a Planned Cesarean Birth

Abstract: Even though a cesarean birth is planned, women may experience physical and psychological difficulties. This qualitative study explored the overall experience of first-time mothers having a planned cesarean birth, which was any cesarean in which the decision was made prior to the onset of labor or labor induction. Eleven primipara postpartum mothers shared their stories. Data were analyzed using Riessman’s method of thematic narrative analysis. Seven overarching themes revealed a need to accept a cesarean birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
(53 reference statements)
2
8
0
Order By: Relevance
“…In a recent descriptive qualitative study, Baxter (2020) found that without appropriate support from staff, a woman's pain and any unexpected interventions in labor had a far greater negative emotional impact. Another recent qualitative study which described first time mother's experiences with cesarean surgery revealed similar feelings of fear related to the unknowns of the operating room, surgical procedures, and anesthesia (Puia, 2018) as were observed in this sample.…”
Section: Discussionsupporting
confidence: 68%
“…In a recent descriptive qualitative study, Baxter (2020) found that without appropriate support from staff, a woman's pain and any unexpected interventions in labor had a far greater negative emotional impact. Another recent qualitative study which described first time mother's experiences with cesarean surgery revealed similar feelings of fear related to the unknowns of the operating room, surgical procedures, and anesthesia (Puia, 2018) as were observed in this sample.…”
Section: Discussionsupporting
confidence: 68%
“…One participant explained, "I wanted desperately to birth vaginally, but I opted for the planned caesarean, as in the end the risk to the baby was much less." These women were willing to forego their own desires for a vaginal birth in order to provide what they felt was the safer alternative for their baby (Puia, 2018).…”
Section: Lived Experiences Of Mothers Who Had Caesarean Section Deliverymentioning
confidence: 99%
“…Thus, regular delivery and cesarean section essentially have a psychological impact on a mother (Puia, 2018). Therefore it is necessary to carry out a model of midwifery care with village midwives and medical midwives.…”
Section: Midwifery Care Model For Childbirth Mothermentioning
confidence: 99%